2009
DOI: 10.1209/0295-5075/87/34002
|View full text |Cite
|
Sign up to set email alerts
|

Physical bounds on the all-spectrum transmission through periodic arrays

Abstract: We show that the blockage in transmission of a screen with a periodic microstructure integrated over all wavelengths is bounded by the static polarizability per unit area of the screen. Physical bounds on the co-polarized transmission coefficient over a wavelength interval are presented using only information from the zero-frequency properties of the microstructure. The theoretical results are compared to and verified by measurements on a screen composed of a large number of split ring resonators printed on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 20 publications
1
46
0
Order By: Relevance
“…Another application of our results is related to [23,24], where it is shown that the transmission through a low-pass slab of thickness d must satisfy (where the plane of incidence coincides with the xz-plane)…”
Section: Applicationsmentioning
confidence: 83%
See 1 more Smart Citation
“…Another application of our results is related to [23,24], where it is shown that the transmission through a low-pass slab of thickness d must satisfy (where the plane of incidence coincides with the xz-plane)…”
Section: Applicationsmentioning
confidence: 83%
“…Expressions were given for the wave parameters in the principal propagation directions, and the polarisabilities were used together with the results from [23,24] to give an upper bound on the product of bandwidth and transmission level for a slab of split-ring material used as a band-stop filter.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements were performed on the same sheet of printed metal split ring resonators on a thin FR4 substrate as in [11]. The unit cell geometry is depicted in Fig.…”
Section: 2mentioning
confidence: 99%
“…In [11], the transverse polarizabilities of the sheet were computed to γ exx /A = 7.2 mm and γ eyy /A = 7.1 mm. The longitudinal polarizability can be estimated by The measured and simulated transmission coecients were then used to calculate the integral in the left hand side of (3.9), and the result is depicted in Fig.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation